Measurement of binding strength between prey proteins interacting with Toxoplasma gondii SAG1 and SAG2 using isothermal titration calorimetry (ITC) - Lai, Meng Yee; Lau, Yee Ling (Springer Verlag (Germany), 2018)
Following the outcome from a previously performed yeast two-hybrid experiment, the binding strength between T. gondii SAG1 and SAG2 and their respective prey proteins were further confirmed in this study. The sag1, sag2 and their prey genes were amplified and cloned into a pGEMT vector. To express the recombinant proteins, the fragments were then subcloned into a pRSETA vector and transformed into E. coli BL21 (DE3) cells. The recombinant proteins were expressed optimally at 37°C and 1mM of IPTG. The 6X His-tag fusion proteins were purified, dialyzed and concentrated. To confirm the expressed proteins, the recombinant proteins were analysed by SDS-PAGE and Western blot. As expected, the size of SAG1, SAG2, HLY and HZF protein were 32, 23, 28 and 37 kDa, respectively. The purified proteins were loaded onto a MicroCal Auto-iTC200 calorimeter from MicroCal™ to quantify binding strength. ITC results indicated there was a typical binding curve for interactions between SAG1 and HLY protein. However, there was an atypical binding curve obtained for interactions between SAG2 and HZF protein. By observing the data obtained from the ITC assay, both of the human proteins (HLY and HZF) were demonstrated to bind to their respective SAG1 and SAG2 proteins.